The role of the African Languages Research Institute in addressing language of instruction dilemmas in Zimbabwe - Masuku, J.; Ndhlovu, F. (Buro van die WAT, 2021)
The lexicographic work of the African Languages Research Institute (ALRI) has played a significant role in attempting to avoid some of the dilemmas associated with using African languages as media of instruction in the Zimbabwean education system. Monolingual Shona and Ndebele dictionaries, biomedical reference works, dictionaries of musical, literary and linguis-tic terms as well as children's dictionaries constitute part of ALRI's contribution towards the goal of mainstreaming African languages in the education system. This article is an evaluation of the research activities taking place at ALRI. The aim of the article is to demonstrate that if they receive adequate attention through corpus planning, African languages possess the capacity to play an important role as media of instruction across the entire spectrum of the education curricula in Zim-babwe and elsewhere. The article concludes by observing that, if the efforts of ALRI are to succeed, there is need for the co-operation of all stakeholders in language practice. Keywords: dictionaries, lexicography, lexicographer, lexicographic research, indigenous african languages, african languages research institute (alri), education, curriculum, medium of instruction, Shona, Ndebele, Zimbabwe